PANDEMI COVID 19 SEBAGAI FORCE MAJEURE TERHADAP PEMUTUSAN HUBUNGAN KERJA SERTA DAMPAK PEREKONOMIAN INDONESIA - Arie Setyo Dwi Purnomo; M. Boy Singgih Gitayuda; Budi Hartono (Universitas Islam Balitar, 2021)
Corona Virus Disease 19 or Covid-19 has spread to many countries, including Indonesia. The Covid-19 pandemic had many impacts on people's lives, especially in the economic sector. Many workers have experienced layoffs or layoffs due to this pandemic. This layoff is considered one of the efficiencies imposed by the company amid the pandemic. However, in this case, sometimes some companies cut off their work relationships during the Covid-19 pandemic, often using force majeure reasons, even though the company is still producing as usual. A situation is said to be force majeure, which is a state of coercion that is beyond the control of the parties concerned. There is a condition if the company can carry out layoffs, which is also contained in the provisions. So in this case, this termination should not necessarily decide unilaterally, especially on the grounds of force majeure. If there is a reason for Termination of Employment, there is a reason according to Article 164 paragraph (3) of Law Number 13 of 2003 concerning Manpower which states that the company can lay off because the company is closed while it turns out that the company continues to produce as usual or because it has suffered a loss for 2 consecutive years even though if it is associated with this Covid-19 pandemic, it has not yet reached 2 years to be said to have been laid off. So that the layoffs include the termination of one of the parties not together. Companies should take steps that can be taken such as reducing wages, reducing work shifts, and restrictions related to overtime work. Therefore, it is necessary to have a comprehensive policy from the government in the event of a force majeure so as not to harm the workers or companies that employ them and reduce the direct economic impact.